2006
DOI: 10.1002/mds.20880
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dystonia in Akita prefecture in Northern Japan

Abstract: We investigated the prevalence of dystonia in Akita Prefecture (population was 1,166,967 as of 1 November 2004). The prevalence of primary generalized and focal dystonia is estimated to be 0.68 and 14.4 per 100,000 persons, respectively. Blepharospasm is the most common primary dystonia in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 8 publications
1
30
1
Order By: Relevance
“…The 15 studies analysed came from Europe (11 studies13–23), Japan (2 studies24 25), India (1 study26) and USA (1 study;27 table 1); all were from the northern hemisphere covering a latitude of 41° (Reykjavik, Iceland at 64.1° to Kolkata, India at 22.6°). Most (13 studies) were service-based except for two epidemiological surveys in northern England13 and India 26.…”
Section: Resultsmentioning
confidence: 99%
“…The 15 studies analysed came from Europe (11 studies13–23), Japan (2 studies24 25), India (1 study26) and USA (1 study;27 table 1); all were from the northern hemisphere covering a latitude of 41° (Reykjavik, Iceland at 64.1° to Kolkata, India at 22.6°). Most (13 studies) were service-based except for two epidemiological surveys in northern England13 and India 26.…”
Section: Resultsmentioning
confidence: 99%
“…The high rate here can be mostly attributed to the intensive case ascertainment, as the authors screened the Reykjavik hospital records for a period of over 50 years. Sugawara et al [14] investigated the prevalence of dystonia in northern Japan and found 177 patients with primary dystonia (169 with focal dystonia). The high prevalence of focal dystonia (144 per million) can be explained by the study design.…”
Section: Discussionmentioning
confidence: 99%
“…However, movement disorders in the context of the emergency room (ER) have been under-recognized and underestimated, despite the disabling features of the disorders. Most previous studies were based on outpatient clinic data and focused on only one type of movement disorder [1,2,18]. Consequently, there is little information about the frequency and causes of the various movement disorders seen in the ER.…”
Section: Introductionmentioning
confidence: 98%